2016
DOI: 10.1021/acs.chemrestox.6b00112
|View full text |Cite
|
Sign up to set email alerts
|

Hop (Humulus lupulus L.) Extract and 6-Prenylnaringenin Induce P450 1A1 Catalyzed Estrogen 2-Hydroxylation

Abstract: Humulus lupulus L. (hops) is a popular botanical dietary supplement used by women as a sleep aid and for postmenopausal symptom relief. In addition to its efficacy for menopausal symptoms, hops can also modulate the chemical estrogen carcinogenesis pathway and potentially protect women from breast cancer. In the present study, an enriched hop extract and the key bioactive compounds [6-prenylnarigenin (6-PN), 8-prenylnarigenin (8-PN), isoxanthohumol (IX), and xanthohumol (XH)] were tested for their effects on e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
78
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(83 citation statements)
references
References 69 publications
5
78
0
Order By: Relevance
“…Although 8-PN was shown to be a potent ERα agonist and to promote proliferation in MCF-7 cells (Helle et al, 2014; Milligan et al, 2000), it is striking that no proliferation was observed in our study. This might be explained by the recently shown AhR agonistic activity of 6-PN (Wang et al, 2016) as several publications described a AhR-ER cross-talk in the uterus comprising a modulation of ER signaling by AhR activation (Buchanan et al, 2000; Shanle and Xu, 2011). The histological analysis of the mammary gland after this 8-week administration of the hops extract did not show any unwanted side effects providing further evidence for the safety of the hops extract (data not shown).…”
Section: Discussionmentioning
confidence: 98%
“…Although 8-PN was shown to be a potent ERα agonist and to promote proliferation in MCF-7 cells (Helle et al, 2014; Milligan et al, 2000), it is striking that no proliferation was observed in our study. This might be explained by the recently shown AhR agonistic activity of 6-PN (Wang et al, 2016) as several publications described a AhR-ER cross-talk in the uterus comprising a modulation of ER signaling by AhR activation (Buchanan et al, 2000; Shanle and Xu, 2011). The histological analysis of the mammary gland after this 8-week administration of the hops extract did not show any unwanted side effects providing further evidence for the safety of the hops extract (data not shown).…”
Section: Discussionmentioning
confidence: 98%
“…ER dependent activity of 8-PN may at least in part be functionally counterbalanced by the activation of AhR. As a molecular basis for this hypothesis, on one side we showed that the AhR family of genes is expressed in target tissues in a sex hormone dependent manner [47,48], and on the other side evidence exists that the hops extract may contain AhR activating, counterbalancing compounds with 6-PN [15] as an example.…”
Section: Discussionmentioning
confidence: 96%
“…Whereas 8-PN is the most potent ERα agonist known among the group of phytoestrogenic compounds [16,17], 6-PN has recently been identified as an AhR agonist thereby inducing cytochrome P450 enzyme 1A1 dependent 2-hydroxylation of estradiol, which is believed to be the non-toxic pathway of estrogen metabolism [15]. It is long known that AhR activation e.g.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Movement of the prenyl substituent from C-8 to C-6 results in a loss of estrogenic activity. Additionally, other prenyl derivatives of naringenin present in hops, such as 6-prenylnaringenin, may play an important role in post-menopausal hormonereplacement therapy, among others being catalysts of regioselective estrogene hydroxylation, which reduces the risk of breast cancer [16].…”
mentioning
confidence: 99%